A-184 Performance Validity Test Failure Rates in Bilingual Individuals Evaluated in English. (30th August 2021) - Davis, Jeremy; Hromas, Gabrielle; Rolin, Summer
Abstract: Objective: Classification accuracy of embedded performance validity tests (PVTs) is unknown in cases involving bilingual examinees evaluated in English. This study examined false positive rates in bilingual individuals in an older adult sample. Method: The project involved secondary analysis of a deidentified dataset (N = 22, 688) from the National Alzheimer's Coordinating Center (NACC). Exclusion criteria were diagnosis of mild cognitive impairment (MCI; n = 5160) or dementia (n = 5550). The initial sample included 11, 513 participants grouped as cognitively normal (89.6%) or impaired but not MCI. A subset of 275 participants was identified with a primary language other than English who were evaluated in English. Propensity score matching was conducted by diagnostic group to match bilingual to monolingual participants on age, education, gender, and MMSE score. The final sample included 450 and 100 participants in normal and impaired groups, respectively. Failure rates on five embedded PVTs in the NACC cognitive test battery were examined by language and by diagnosis. Results: Age, education, gender, and MMSE score were not significantly different by language in either diagnostic group. In the normal group, 4.9% of bilingual and 2.2% of monolingual participants failed two or more PVTs (n.s.). In the impaired group, 12% of bilingual and 6% of monolingual participants failed two or more PVTs (n.s.). Conclusions: PVT failure rates were not significantly different between bilingual participants evaluated in English and monolingual participants in either diagnostic group. Failure rates, however, increased slightly above a common false positive threshold of 10% in bilingual participants in the impaired group.